A model for cost estimation of system for piggery wastes treatment ponds: a case study - Medri,Waldir (2003)
This article presents the results from the monitoring of a system of ponds for the treatment of piggery wastes, carried out during a 20 months period, with the objective to determine design parameters for the optimization of the treatment system. A series composed of two anaerobic ponds, one facultative pond and one water hyacinth pond, gave an efficiency of 97% in the removal of BOD5, 93% for total phosphorus, 91% for total Kjeldahl nitrogen and a removal of 7 log units for fecal coliforms. A model of the optimization incurred in the treatment of these wastes was developed, within economic concepts.